Gauging DNA degradation among common insect trap preservatives. Issue 3 (9th January 2023) - Ruppert, Laura‐Sophia; Segelbacher, Gernot; Staab, Michael; Winiger, Nathalie
Abstract: Genetic methods for species identification are becoming increasingly popular and can accelerate insect monitoring. However, obtaining good DNA quality and quantity from insect traps remains a challenge for field studies. Ethylene glycol, propylene glycol, and Renner solution have been previously suggested as suitable preservatives for the collection of genetic material, but a systematic overview of their performance under compromising field conditions is lacking. Here we experimentally test whether and how different preservatives affect DNA quality under different conditions and evaluate how choice of preservative may affect metabarcoding and more demanding downstream applications (e.g., RADseq). For this, we used the house cricket, Acheta domesticus (L.) (Orthoptera: Gryllidae), and tested propylene glycol, ethylene glycol, and Renner solution for their ability to preserve DNA over 27 days in various dilutions and temperatures. DNA quality was measured as DNA fragmentation and success rates in PCR amplifying a COI fragment of 658, 313, or 157 bp. Undiluted propylene glycol and ethylene glycol always retained high molecular weight DNA at room temperature. No high molecular weight DNA was preserved at 37 °C or in any dilution. Nevertheless, the COI sequence could be amplified from samples at every condition. Renner solution did not preserve high molecular weight DNA and fragmentation increased over time at 37 °C until amplification was impossible. The results suggest that propylene glycol and ethylene glycol are suitable preservatives for collecting both genetic and morphological material, but dilution or high temperatures compromise their ability to preserve high molecular weight DNA. For genomic approaches requiring high DNA quality, additional preservatives may need to be tested. Abstract : Building up on recent literature recommending propylene glycol, ethylene glycol, and Renner solution for the collection of genetic material, we investigated the limitations of these preservatives with temperature and dilutions, over a period of 27 days, using Acheta domesticus (Orthoptera: Gryllidae). The preserving capabilities of propylene and ethylene glycol are severely impaired by higher temperature and dilution, and Renner solution fails to preserve DNA entirely at higher temperature. This highlights a need for systematic stress testing of insect trap preservatives.